The Designing Registration System and Exam Schedule for Pusat Kegiatan Belajar Masyarakat (PKMB) Business Tips Training - Saputra, Maulian; Saragih, Juliyandri; Susilawati (Bahasa Indonesia, 2023)
Pusat Kegiatan Belajar Masyarakat (PKBM) Kiat Usaha is a non-formal educational institution that provides learning opportunities for the general public who wish to pursue formal education, especially in preparation for equivalency exams. One of the challenges faced by PKBM Kiat Usaha is managing registration data and exam schedules which are still done manually and inefficiently. Therefore, this research aims to design a web-based registration information system and exam schedule that can simplify and speed up the administration and communication process between prospective students and admin. The method used in this research is the waterfall method which consists of five stages, namely needs analysis, system design, system implementation, system testing, and system maintenance. The result of this research is a web-based registration and exam schedule information system which has features such as online registration, payment confirmation, exam schedule settings, exam results announcements, and student data reports.